The Role of Notary and PPAT in Making Inheritance Deed for Non-Muslim Heirs (International Journal of Scientific Research and Management (IJSRM), 2019)
The problem of inheritance is still a complex matter in Indonesia. In general, the transfer of inheritance is carried out in several ways, namely inheritance, grant and will. Provisions regarding inheritance are regulated in the Civil Code, KHI and various jurisprudences which can be used as a foundation. In carrying out the distribution of inheritance is also inseparable from the role of Notary and PPAT which by Law Number 30 of 2004 concerning Notary Position and Government Regulation Number 37 of 1998 concerning PPAT Position Regulations, the regulation is given the authority to make deeds. The method used in the study is the empirical research method. In order to find out the position of non-Muslim heirs in Islamic inheritance, and to find out how the role of Notary and PPAT and the form of deed made in the distribution of the inheritance.